(untitled) (LEARNing Landscapes, 2016)
This paper presents an arts-integrated process for teacher educators to engage their students in critical thinking, meaning-making, and knowledge construction in order to enable pre-service teachers to analyze metanarratives that inform their teacher identities. The research team used the Parallaxic Praxis research model to frame its art-making investigations in a practice-based research process. The three researchers each created an artefact as part of their individual inquiry of the data set, comprising 90 material cloaks created by pre-service teachers, to enter into dialogue addressing the prevailing metanarratives expressed by the pre-service teacher participants.